Effect of Bond Age, Interest Rate and Inflation Level of Bond Results - Elsye Fatmawati (Journal of Research in Business, Economics, and Education, 2020)
Bonds are chosen by investors as investment instruments because they have a fixed return in the form of interest or coupon bonds and yields with a low level of risk. The purpose of this study was to determine the relationship and influence of bond age, interest rates and inflation on bond yields. The methodology used in this study is quantitative research design. The sample of this study is conventional government bonds listed on the IDX in 2018 determined using the purposive sampling method. Data analysis method used in this research is quantitative data analysis to calculate and estimate quantitatively some independent variables on the dependent variable partially or simultaneously. The results in this study indicate that partially the age of bonds does not have a significant effect on government bond yields, partially the interest rate has a significant effect on government bond yields and partially inflation does not have a significant effect on government bond yields. While simultaneously the age of bonds, interest rates and inflation have a significant effect on the yield of government bonds listed on the IDX in 2018.